Communication in the Era of Attention Scarcity
X, 143 p. 1 illus.
Keywords: This book examines a series of phenomena that have accompanied the development of digital technology and focuses on the attentional processes that these phenomena have in common. Across the social order, complaints are growing about a lack of attention as well as an overriding push by corporations and institutions to capture and mobilize attention. With a particular focus on social attention, the book highlights the need for an increased awareness about the agents that shape attention in our society, the effects that these agents (attempt to) produce, and the means by which individuals and groups may increase their control overpersonal and social attention. With a range of academic perspectives, this book is a crucial read for understanding the changing shape of political, business and personal communication.